2009
DOI: 10.1007/s11123-009-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in Islamic and conventional banking: an international comparison

Abstract: Islamic banking, International efficiency comparison, Output distance function, G21, D24, L1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 51 publications
7
75
1
2
Order By: Relevance
“…The main sizeable body of studies has explained the general Islamic principles and the product used in Islamic banking (Bashir, 1983;Khan, 1985;Siddiqi, 2006: Sundararajan & Errico, 2002. Current researches have discussed the management, regulatory and supervisory challenges associated with Islamic banking (Daly & Frikha, 2015;Jobst, 2007;Murjan & Ruza, 2002;Sole, 2007) the efficiency of IBs using frontier analysis approaches such as data envelopment analysis and stochastic frontier analysis (Abdul-Majid et al, 2010;Belanes & Hassiki, 2011;Srairi, 2010), the characteristics and profitability of IBs (Abedifar, Molyneux, & Tarazi, 2013;Beck et al, 2013;Ben Khediri & Ben-Khedhiri, 2009;Karim & Ali, 1989;Srairi, 2008), and whether it is possible to distinguish between IBs and CBs (Iqbal, 2001;Metwally, 1997;Olson & Zoubi, 2008). Another strand of literature studied the soundness, resilience and financial stability of IBs during the global financial crisis (Abedifar, Philip, & Amine, 2013;Beck et al, 2013;Bourkhis & Nabi, 2013;Caby & Boumediene, 2013;Čihák & Hesse, 2010;Daly, Ghorbel-Zouari, & Frikha, 2013;Hasan & Dridi, 2010).…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main sizeable body of studies has explained the general Islamic principles and the product used in Islamic banking (Bashir, 1983;Khan, 1985;Siddiqi, 2006: Sundararajan & Errico, 2002. Current researches have discussed the management, regulatory and supervisory challenges associated with Islamic banking (Daly & Frikha, 2015;Jobst, 2007;Murjan & Ruza, 2002;Sole, 2007) the efficiency of IBs using frontier analysis approaches such as data envelopment analysis and stochastic frontier analysis (Abdul-Majid et al, 2010;Belanes & Hassiki, 2011;Srairi, 2010), the characteristics and profitability of IBs (Abedifar, Molyneux, & Tarazi, 2013;Beck et al, 2013;Ben Khediri & Ben-Khedhiri, 2009;Karim & Ali, 1989;Srairi, 2008), and whether it is possible to distinguish between IBs and CBs (Iqbal, 2001;Metwally, 1997;Olson & Zoubi, 2008). Another strand of literature studied the soundness, resilience and financial stability of IBs during the global financial crisis (Abedifar, Philip, & Amine, 2013;Beck et al, 2013;Bourkhis & Nabi, 2013;Caby & Boumediene, 2013;Čihák & Hesse, 2010;Daly, Ghorbel-Zouari, & Frikha, 2013;Hasan & Dridi, 2010).…”
Section: Regression Resultsmentioning
confidence: 99%
“…In fact, during this crisis, although IBs showed their performance, Bashir (2000), their profitability Bashir and Hameed (2003), and their stability Cihak and Hesse (2008), Čihák and Hesse (2010), some studies quote that IBs do not have any advantages in efficiency and stability (Kuran, 2004). The relative efficiency of those non-usurious banks is appreciated by the following studies (Abdul- Majid, Saal, & Battisti, 2010;Darrat et al, 2002;ElGamal & Inanoglu, 2005;Hassan, 2005;Sufian & Akbar Noor Mohamad Noor, 2009;Srairi (2010). Moreover, as shown in recent research, Ben Khediri, Charfeddine, and Ben Youssef (2014) found that the financial crisis has a negative impact on both IBs and CBs but time shifted.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Yet the Islamic banking system, due to constraints imposed by Shariah law, is less efficient than the conventional one (Johnes et al 2014;Abdul-Majid et al 2010) 4 Empirical results…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…The emergence of Islamic banking has been driven by the increasing number of Muslims who wish to lead their lives according to the Shariah, the legal code of Islam (Abdul-Majid, Saal, & Battisti, 2010). The existence of Islamic banks in the second half of the 20th Century came as an offshoot of the newly rediscovered Islamic economics (Kahf, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The salient features of Islamic banking are the prohibition of interest payment in transactions, and the prohibition of undertaking or financing anti-social and unethical behaviour such as gambling, pornography and alcohol (Abdul-Majid, Saal, & Battisti, 2010).…”
Section: Introductionmentioning
confidence: 99%